Upaya meningkatkan hasil belajar siswa melalui penerapan model pembelajaran discovery learning - Dian Mayasari; Tasrini Dwi Lestari; Jualian R Untajana (Journal of Didactic Mathematics, 2023)
The application of the Discovery Learning learning model aims to create activity-based learning discoveries that will have an impact on improving student learning outcomes. This type of research is research class action using the Kemmis and Mc Taggart models. This research was conducted at SMK Negeri 2 Merauke, which focuses on mixed class XI, has 11 students in odd semesters. The purpose of this activity to improve learning activities so that they can run effectively according to conditions. Research instruments that used in the form of teacher observation sheets, student observation sheets and student test sheets. Observation sheet for measure the effectiveness of learning activities and test sheets are used to measure student learning outcomes. This research was conducted through 2 cycles. The results of this study is an increase in learning activities students marked by the average percentage of student activity in cycle 1 of 42% (enough) rose to 70% (good) in cycle 2. Student learning activities influence student learning outcomes indicated by the presence of an average percentage of completeness learning outcomes cycle 1 of 0% (low) increased to 72.7% (good) in cycle 2.